What Factors Influence the Determination of Audit Fees - Ellyanna Junita; Devica Pratiwi (Dinasti International Journal of Economics, Finance & Accounting, 2023)
The purpose of this study is to test the influence of variables that are factors in determining the value of audit fees in food and beverage sub-sector manufacturing companies listed on the IDX for the 2017-2021. This study focuses on four independent variables, company complexity, internal audit, profitability, and company risk, and one dependent variable, audit fee. The collected data was further processed using purposive sampling techniques, resulting in a population of 12 companies or as many as 300 samples. Then, these data were processed with IBM SPSS software version 25, and it was found that the complexity of the company had a positive and significant effect on the audit fee, the internal audit had a negative and significant effect on the audit fee, and the company's profitability and risk did not affect the audit fee.